(untitled) (Contemporary Mathematics, 2024)
Artificial Intelligence Solution is given for Relaxation Oscillation Equation, which is one of the simplest Fractional Differential Equation. Artificial Intelligence solution has been identified as the best one for fractional differential equation. Sample for patterns of fractional different equation are extracted. The better performance of Machine Learning Models is compared with the Numerical solution of Successive Approximation Method and reported.